2020
DOI: 10.1021/acschemneuro.0c00246
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like Effect of Merazin Hydrate Depends on NO/ERK by Suppressing Its Downstream NF-κB or Nonactivating CREB/BDNF in Mouse Hippocampus

Abstract: Merazin hydrate (MH), an essential ingredient of Fructus aurantii, has been identified to have an antidepressant-like effect. However, the molecular mechanisms of MH modulate depressive behavior are largely uncharacterized. Here, in lipopolysaccharide-induced mice, we identified that a single administration of MH recovered depressive behaviors and down-regulated the expressions of neuronal nitric oxide synthase (nNOS) in the hippocampus after 1 day. Activation of nNOS by l-arginine led to depressive behaviors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
3
5
0
Order By: Relevance
“…The results showed that LH increased all of them significantly, which were all reversed by a single administration of MH at 2 h [Figure A–C; ANOVA, eNOS: F (3, 31) = 12.00, p < 0.001; IL-10: F (3, 31) = 8.25, p = 0.004; TNF-α: F (3, 31) = 26.35, p < 0.001], which was similar to ketamine. The results were consistent with our previous studies, which were revealed in LPS-induced mice in serum . Mounting evidence suggests that inflammation may play a key role in the etiology of depression .…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The results showed that LH increased all of them significantly, which were all reversed by a single administration of MH at 2 h [Figure A–C; ANOVA, eNOS: F (3, 31) = 12.00, p < 0.001; IL-10: F (3, 31) = 8.25, p = 0.004; TNF-α: F (3, 31) = 26.35, p < 0.001], which was similar to ketamine. The results were consistent with our previous studies, which were revealed in LPS-induced mice in serum . Mounting evidence suggests that inflammation may play a key role in the etiology of depression .…”
Section: Resultssupporting
confidence: 92%
“…Previously, we found that MH was capable of producing rapid antidepressant-like effects in lipopolysaccharide (LPS)-induced mice in the hippocampus, which depended on reliving neuroinflammation . However, the rapid antidepressant-like effects of MH are similar to those of some classic rapid antidepressant drugs, such as ketaminestill unclear.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations